Do remote areas benefit from economic growth? Evidence from Uganda - Daniels, Lisa; Minot, Nicholas (John Wiley & Sons, 2021)
One of the most universal patterns in the spatial distribution of poverty in developing countries is that the incidence of poverty is lower in urban areas than in rural areas. It is widely accepted, though less well documented, that remote rural areas tend to be poorer than areas with good market access. Furthermore, there is concern that remote rural areas may not benefit equally from economic growth. In this paper, we examine poverty trends in rural Uganda to test whether remote rural areas benefit from economic growth to the same degree as better connected rural areas. Applying a variant of small‐area estimation methods to household survey data and several Demographic and Health Surveys carried out over 10 years, we confirm that remote rural areas are poorer than better connected rural areas, but find no evidence that they have fallen further behind over this period.